Assessing the link between financial soundness and systemic risk for key Russian banks - Александр Маркович Карминский; Михаил Иосифович Столбов (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2016)
Alexander Markovich Karminsky - National Research University "Higher School of Economics". Email: akarminsky@hse.ruMikhail Iosifovich Stolbov - Moscow State Institute of International Relations, Ministry of Foreign Affairs. E-mail: stolbov_mi@mail.ruThe paper introduces the approach to assessing the link between two sets of indicators – financial soundness and systemic risk. It is based on canonical correlation analysis and applies to key publicly traded Russian banks – Sberbank and VTB for the period 2010:1q-2015:3q. The financial soundness indicators are sourced from quarterly financial statements while systemic risk measures come from the Center for Risk Management database (HEC Lausanne).The methodology is instrumental both in measuring linear dependencies between two sets of indicators and as a tool of factor analysis, enabling to identify the most influential variables within these sets. Namely, for the banks in question very high positive correlations are observed between financial soundness and systemic risk. The ARDL estimator and bounds cointegration test show that systemic risk leads the set of financial soundness indicators. The finding can largely be attributed to the underlying high frequency structure of systemic risk data while financial soundness is discrete and measured on quarterly basis. It also accentuates the importance of monitoring systemic risk for Russian banks. The SRISK metric corresponding to the capital shortfall as a result of the 40% decline of the world stock market appears to play a pivotal role within the set of systemic risk indicators.